Chronic kidney disease in hypertensive patients: the urgent need for targeted interventions in Arab countries: a systematic review - Al Rashdi, Fakhria; Tabche, Celine; Atwan, Zeenah; Al-Qanubi, Hamed; Al Khaldi, Samiya; Al-Zadjali, Nasrin; Rawaf, Salman (Frontiers in Nephrology, 2026)
BackgroundChronic kidney disease (CKD) is expected to be the 5th leading cause of years of life lost by 2040. Recently, it emerged as a significant cause of mortality and morbidity, with a high prevalence in Arab countries.ObjectiveAssess CKD among hypertensive (HTN) people in Arab Countries through evaluation of the existing literature on CKD prevalence, risk factors, screening programmes and prevention.Study designA systematic review till April 2024 following PRISMA guidelines. The search strategy was registered in PROSPERO under the identification code CRD42024486068.MethodsDatabases searched were Medline, Embase, Scopus, PubMed, Cochrane Library. Screening was done using Covidence by three independent reviewers.ResultsOut of 63 studies screened, 11 were selected for extraction. The prevalence of CKD was higher among elderly, HTN and diabetic patients, with 38.8% having unrecognised CKD. Nearly 39% of the 400 participants in one study had undiagnosed stages 3–5 CKD. Two studies showed that 55.8% and 75% of identified CKD patients had HTN. Physicians reported suboptimal screening rates, with about 77% relying on the estimated glomerular filtration rate as a diagnostic tool. Risk factors for CKD include old age, HTN, dyslipidaemia, family history of CKD, and obesity. Among physicians, 85% recommended a target blood pressure of ≤130/80, 80% advised smoking cessation, 66% prescribed anti-lipids, and 67% recommended weight loss. All studies support the fact that HTN is a risk factor for CKD.ConclusionCKD is an escalating problem in Arab countries, with hypertension as a major risk factor. Many patients remain undiagnosed. A region-specific CKD screening and HTN control programme is urgently needed. The findings are essential for policymakers in strengthening primary care for systematic screening of HTN and CKD.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024486068.